Dark angel - Andrews, V. C. (Virginia C.) (London : Harper Collins, 1993)
When Heaven Leigh Casteel moves in with her wealthy grandmother, she believes she has found a place to belong and an opportunity to make something of herself until she begins to realize the terrible truth beneath the glamorous facade of her grandmother's life.
Sequel to: Heaven.
Adult.
Keywords: Family problems -- Fiction; Grandmothers -- Fiction; Family problems -- Fiction; Grandmothers -- Fiction